Application of aerophotogrametry in inventory poplar plantation - Borota Dragan; Pantić Damjan (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2023)
In the forest stand-wise inventory of Serbia, data is obtained using terrestrial methods - using complete (total) and partial measurement. Foreign experiences show that part of the information about forests can be obtained on the basis of aerial images - using aerial photogrammetry methods. In this sense, the goal of this work was to assess the possibility of applying aerial photogrammetry in the process of collecting information in poplar plantations, planting spacing 5 x 5 m, aged 10, 15, 20 and 25 years. The reliability of data obtained on the basis of air images was determined by comparison with data obtained by terrestrial measurement. The results of the research only partially confirmed foreign experiences about the possibility of applying aerial photogrammetry in forest inventory. A comparative analysis of the numerical elements of the stand read directly from the images, such as the number of trees, height and crown area, and derived elements - diameter on breast height, basal area and volume of the stand in relation to the values obtained by terrestrial surveying methods, indicated the possibility of limited use of aerial photogrammetry in the inventory of these forests. The differences were reflected in the reading of lower values of crown areas and tree heights, which is why mathematical models predicted lower values of diameters on breast height. This was reflected in the displacement of the tree distribution to lower diameter degrees, consequently leading to differences in the basal area and the volume of the researched plantations in relation to the values obtained by terrestrial surveying. Therefore, as an optimal solution in specific conditions, a combined inventory is imposed, which sublimates the positive characteristics of the tested methods.